Analogi Sebagai Kekuatan Dakwah KH. Zaenuddin MZ: Penerapan Model Rethorical Discourse Analysis Bitzer - Zakaria, Zakaria; Hudri, M.; Khoirotun, Pia; Fatiman (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2025)
This study investigates the patterns of analogical reasoning in the sermons of KH. Zainuddin MZ using Bitzer’s Situational Analysis, which consists of exigence, audience, and constraints. The data were drawn from ten sermons addressing themes of morality, faith, and socio-religious issues. The findings indicate that exigence is the dominant rhetorical force shaping the emergence of analogies (60%), particularly as a response to moral decline, ethical problems, and social phenomena that require religious guidance. The audience dimension (20%) is reflected in the use of analogies closely tied to the daily experiences of Indonesian Muslims—agriculture, commerce, nature, and urban life—thus enhancing clarity, relevance, and emotional resonance. Meanwhile, constraints (20%) appear through cultural norms, ethical boundaries, and the preacher’s distinctive style, characterized by politeness, humor, and communicative clarity. The study concludes that the effectiveness of KH. Zainuddin MZ’s preaching lies in his ability to link social urgencies with the concrete experiences of his listeners while maintaining ethical and cultural coherence. These findings contribute to the field of Islamic rhetorical studies by demonstrating how rhetorical situations shape analogical strategies in religious communication.   Penelitian ini menganalisis pola penggunaan analogi dalam ceramah KH. Zainuddin MZ dengan menggunakan kerangka Analisis Situasional Bitzer, yang mencakup exigence, audience, dan constraints. Data diperoleh dari sepuluh ceramah bertema akhlak, keimanan, dan persoalan sosial keagamaan. Hasil penelitian menunjukkan bahwa exigence merupakan unsur dominan yang membentuk lahirnya analogi retoris (60%), terutama sebagai respons terhadap problem moral masyarakat, degradasi etika, serta fenomena sosial yang membutuhkan pengarahan dakwah. Unsur audience (20%) tercermin melalui pemilihan analogi yang dekat dengan pengalaman hidup jamaah, seperti dunia pertanian, perdagangan, alam, dan dinamika masyarakat urban, sehingga meningkatkan pemahaman dan kedekatan emosional. Sementara itu, constraints (20%) tampak dari batas nilai, norma budaya Betawi, serta etika dakwah yang dijaga KH. Zainuddin MZ, termasuk gaya komunikasinya yang santun, humoris, dan komunikatif. Penelitian ini menegaskan bahwa efektivitas dakwah KH. Zainuddin MZ didukung oleh kemampuannya menghubungkan urgensi sosial dengan pengalaman konkret pendengar, sekaligus menjaga pesan tetap berada dalam batas etis. Temuan ini memperkaya kajian retorika dakwah dan menunjukkan bagaimana situasi retoris membentuk strategi analogi dalam komunikasi keagamaan.